Clinical and laboratory profile of Zika virus infection in dengue suspected patients: A case series - Fernanda Estofolete, Cássia (2016)
Background: The Zika virus (ZIKV) is an emerging arthropod-borne virus related to the dengue virus (DENV), and shows a similar clinical profile as other arboviral diseases, such as dengue and chikungunya virus (CHIKV). Historically, ZIKV has been associated with sporadic cases of human infection, but is now responsible for outbreaks worldwide. In Brazil, cases have been reported since 2015, with some cases causing severe disease. Objective: To identify clinical symptoms of Zika in patients in Dengue suspected patients. Study design: Description of a series of cases, wherein we analyzed 100 clinical samples collected from patients who exhibited acute febrile disease for ≤5 days, from January to February 2016. Results: In this study, we report 13 cases of ZIKV infection in adults presenting dengue-like symptoms in a DENV endemic area. All patients presented with fever, with myalgia being the second most frequently observed symptom. Two patients had rashes, but none of them had conjunctivitis. Other less frequent manifestations included headache, arthralgia, diarrhea, and nausea. Conclusion: The co-circulation of ZIKV and DENV is a serious public health concern, since it represents both a clinical and diagnostic challenge in endemic areas, as well as in the field of travel medicine.